ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK PENGUSAHA KECIL ORANG PRIBADI - Azhari S; Devi Safitri (Universitas Sarjanawiyata Tamansiswa, 2020)
This study examines the relationship of taxpayer compliance represented by the modernization of the tax administration system, tax sanction, understanding tax regulations and level of education. This research is a survey of peneltian by spreading the questionnaires and the data used is primary data. The population of this research is taxpayers of small-scale private entrepreneurs in KPP Pratama Pekanbaru Senapelan in 2019 with a turnover of less than 4,800,000,000 per year. The sample selection using the method of simple random sampling and the sample size is calculated by using the formula Slovin so obtained 100 respondents. The data analysis method used is Multiple Linear Regression Analysis by finding that partially modernizing of the tax administration system, taxation sanctions, understanding taxation regulations and level of education have a significant effect on tax compliance of small-scale private entrepreneurs in KPP Pratama the Pekanbaru Senapelan KPP.